Evaluation of MRI Versus Arthroscopy in Anterior Cruciate Ligament and Meniscal Injuries - Amreen Abdul Bari; Shivali Vaibhav Kashikar; Bhushan Narayan Lakhkar; Mohammad Saleem Ahsan (Journal of Clinical and Diagnostic Research, 2014)
Aims and Objectives: To find out the incidence of ACL & meniscal injuries, to co-relate MRI findings with arthroscopy by calculating Sensitivity, Specificity, Positive And Negative Predictive Values (PPV & NPV) keeping arthroscopy as a gold standard, to find out the degree of subluxation and to grade it and to find a threshold value of fluid in knee. Settings and Design: Prospective analytical study. Materials and Methods: MRI of 230 patients with 71 arthroscopic co- relation in year 2012-14 was analysed. Statistical Analysis: Descriptive statistics using Chi square test and predictive values was done. The spearman correlation coefficient was done by using statistical software SPSS 17.0. Results: The sensitivity, specificity, PPV and NPV was calculated (in %). For ACL it was 87.87, 81.57, 80.55, 88.57 for MM 93.54, 87.50, 85.29, 94.59 and for LM 77.77, 81.81, 72.41, 85.71 respectively. We found 35.6% incidence of anterior tibial subluxation with maximum patients having grade 1 category subluxation. Two hundred and one cases showed joint fluid in lateral aspect of the suprapatellar pouch (AP diameter >10mm) with internal derangement. Conclusion: MRI is helpful in diagnosing meniscal and cruciate ligament injuries. Arthroscopy still remains gold standard for definitive diagnosis.